(untitled) (Journal of Political Science and International Relationship, 2025)
This paper emerges from a doctoral research study investigating the potential of investing in Productive Assets (PA) as a strategic intervention to combat household food insecurity in Mudzi Rural District, Zimbabwe. The study arose against a background of persistent food insecurity in Mudzi Rural District, which is exacerbated by climate change and poses severe challenges to rural households, limiting their access to stable and productive resources and livelihoods for food security. Over the years between 2019 and 2024, climate change impact has exacerbated food insecurity in rural communities of Zimbabwe, with Mudzi rural communities experiencing recurrent and severe climate shocks in the form of droughts, flash-floods, storms, extreme temperatures and disease outbreaks that affected both crops and livestock-based livelihoods. These events heightened community vulnerabilities, destabilised livelihoods, and threatened food availability, access and stability, forcing many households to rely on humanitarian assistance. Against this backdrop, the objective of the study was to examine the impact of investing in Productive Assets (PA) on household food security in Mudzi Rural District, investigating the impact of PA investments and strategies for improving household food security outcomes; and informing the development of a household food security promotion model in rural communities. Having been grounded in the Entitlements Theory and the Sustainable Livelihoods Framework, the study intended both to find affirmation on the foundational importance of productive assets in achieving (household) food security and to confirm whether these two frameworks were applicable in the study. In this regard, this paper presents the findings for the discussion and analysis conducted on the applicability of the Sustainable Livelihoods Framework and Entitlement Approach to the promotion of household food security in Mudzi Rural District. The literature on the two frameworks was examined in light of their applicability, providing a theoretical framework for examining household food security through investments in productive assets. Overall, this paper makes the case that, despite the two theories’ limitations in terms of fully applying to the study’s scope, they offer important frameworks and guidance to position PA investments as essential to enhancing household food security by improving access to entitlements, enhancing various aspects of community food production processes, and taking into account important risks and institutional requirements that result in improved food accessibility, availability, utilization, and stability.